Notion and operation of back-to-back clauses in construction subcontracts - Vásquez Rebaza, Walter (2021)
Nowadays, it is not uncommon for general contractors to seek to govern their legal relationships with some of their subcontractors through back-to-back provisions. The principles that guide this type of agreements do not have a univocal logical-conceptual development, so their scope always depends on the intensity that, by virtue of their freedom of contract, the parties assign to the particular drafting of each subcontract. Despite this, it is currently possible to realize that there is a common minimum ground that describes the backbone of this kind of agreement. In the present article, which is part of a more extensive study in progress, we will refer to the aforementioned basic structure of backto-back construction agreements. We will describe these agreements using three principles in which they could be broken down and which guide their development (the principle of “mirror contract”, the principle of “adequacy”, and the principle of “waterfall conditioning”). For this purpose, we will evaluate how these principles are applied in complex transactions carried out in our country. In this context, and because it is absolutely relevant, we will explore the developments of back-to-back in the models of civil law, common law and the FIDIC’s Conditions of Subcontract for Plant and Design-Build (2019).